The Effect of Frying Temperature and Time on the Physical and Chemical Qualities of The Restructured Goat Meat Trimming - Rini Mastuti (Jurnal Ilmu dan Teknologi Hasil Ternak (JITEK), 2008)
The using of frying method at different temperature and time of frying could affect the physical and chemical qualities of the processed meat product. The aim of study was to obtained the best quality of restructured goat meat trimming for the physical and chemical point of view. The research was designed in Randomized Block Design. The raw restructured goat meat trimming product that used in the experiment was used 0.5% carragenan. The product was used in the experiment were frying temperature, namely, 150±20C and 160±20C, and the frying time of 2, 4 and 6 minutes, respectively. The results showed that frying a 1500C for 6 minutes could produce the best fried restructured meat in which contained of 48.89% protein, 16.87% fat, 26.06% moisture content, 74.236% amino acid content, with a binding strength of 15.90 N.   Keywords : frying, protein content, binding strength, fat content,  moisture content